2023
DOI: 10.3390/jcm12051981
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Oral Antidiabetic Drugs in Patients with Type 2 Diabetes: Systematic Review and Meta-Analysis

Abstract: Poor adherence to oral antidiabetic drugs (OADs) in patients with type 2 diabetes (T2D) can lead to therapy failure and risk of complications. The aim of this study was to produce an adherence proportion to OADs and estimate the association between good adherence and good glycemic control in patients with T2D. We searched in MEDLINE, Scopus, and CENTRAL databases to find observational studies on therapeutic adherence in OAD users. We calculated the proportion of adherent patients to the total number of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 215 publications
0
3
0
Order By: Relevance
“…Recent diabetes international guidelines and published studies provide recommendations for personalized treatment decisions, based not only on achieving optimal glycemic control, but also on patient lifestyle, personal preferences, and perception of the proposed therapy. Poor adherence to the treatment can result in treatment failure and an increased risk for complications [ 42 ]. A study conducted in Poland (DIABCON) indicated that only 65.1% of patients were compliant with the self-monitoring of blood glucose [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent diabetes international guidelines and published studies provide recommendations for personalized treatment decisions, based not only on achieving optimal glycemic control, but also on patient lifestyle, personal preferences, and perception of the proposed therapy. Poor adherence to the treatment can result in treatment failure and an increased risk for complications [ 42 ]. A study conducted in Poland (DIABCON) indicated that only 65.1% of patients were compliant with the self-monitoring of blood glucose [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unsatisfactory compliance with antidiabetic medications has been observed in T2DM patients globally [10]. In India, studies with varying criteria for medication adherence have estimated medication non-compliance among diabetes patients to range from 20.5% to 66% [5,[11][12][13][14].…”
Section: Review Poor Medication Adherence and Its Consequencesmentioning
confidence: 99%
“…At an individual level, the economic burden, in addition to safety, efficacy, and ease of administration, is a major factor associated with a lack of medication adherence [20]. This trait is observed in a significant proportion (36.9%-75.1%) of T2DM patients [10,21,22] and could hasten the onset of diabetic complications. The direct costs of T2DM management include medical and nonmedical expenses borne by individuals and families, while the indirect costs include loss of productivity, among others [23].…”
Section: Importance Of Pharmacoeconomic Profile In T2dmmentioning
confidence: 99%